Comparative studies of the differences between flipped class and traditional class in orthopedic surgery education - Wang, Lianlei; Xia, Yanni; Qiu, Cheng; Yuan, Suomao; Liu, Xinyu (Frontiers in Education, 2024)
Objective: This study aims to compare the differences between traditional class teaching model and novel flipped class model in orthopedic surgery, and further clarify the potential merits.Methods: Total 138 undergraduate fourth-year students from Shandong University who interned in the Orthopedics Department of Qilu Hospital from June 2022 to June 2023 were enrolled. They were randomly classified into traditional class group and flipped class group. At the end of the internship, all undergraduate students were evaluated in terms of orthopedic theoretical knowledge and practical operations. In addition, they also filled out subjective questionnaires related to satisfaction with related courses. All parameters involving two groups were compared.The theoretical assessment score of traditional class group was 75.10±9.43, while the theoretical assessment score of the flipped class group was 78.70±10.71, with a statistically significant difference (p=0.038). Compared with the traditional class group (81.52±8.50), the flipped class group showed a significant improvement in skill assessment scores (85.55±8.29), with a statistically significant difference (p=0.006). According to the weighted average score calculation, total score of students in the flipped class group (82.12±6.69) was also higher than that in the traditional class group (78.31±6.05), and the difference was statistically significant. Compared with the traditional class group, the satisfaction survey results of students in the flipped class group showed a significant improvement (except for reduce the learning burden), and the difference was statistically significant (p＜0.05).The flipped class teaching mode significantly improves the learning interest and efficiency of internship students in orthopedic clinical teaching, and increases more communication and understanding between students and teachers. At the same time, it can tap into students' interests, hobbies, and self-learning abilities, effectively improving their mastery of theoretical knowledge and skill operations, which is worth promoting.